Types, design, implementation, and evaluation of nutrition interventions in older people in Africa: A scoping review protocol. - Anthony Manyara; Tadios Manyanga; Rudo Chingono; Shane Naidoo; Kate Mattick; Grace Pearson; Opeyemi Babatunde; Niri Naidoo; Kate A Ward; Celia L Gregson (PLoS ONE)
Introduction Africa's older population is increasing and this, necessitates the development of interventions to promote healthy ageing. Nutrition is a key determinant of healthy ageing and local contextual evidence is needed to inform nutritional intervention development in Africa. There are already reviews on nutritional status and food insecurity in older adults in Africa. However, a synthesis of nutrition interventions targeting older people specifically, is lacking. Therefore, this protocol describes a scoping review that aims to systematically synthesise current evidence on nutrition interventions for older people in Africa. Methods The review will involve: a review of available reviews on nutrition in older people in Africa (Phase 1); a review of nutrition interventions developed or implemented among older people in Africa (Phase 2); and consultation with local nutrition stakeholders in Zimbabwe, and The Gambia to contextualise Phase 1 and 2 findings and solicit insights not in the published literature (Phase 3). Searches for Phases 1 and 2 will include bibliographic databases (MEDLINE, EMBASE, Web of Science, African Journals Online, African Index Medicus) and grey literature sources (i.e. relevant websites). Title, abstract, and full-text screening will be conducted in duplicate, data extracted using piloted tools and findings summarised using descriptive statistics and narrative text. Phase 3 will be conducted using hybrid workshops, audio-recorded, detailed notes taken, and findings combined with those from Phases 1 and 2. Conclusion The findings of this review will summarise current evidence on nutrition in older people in Africa and inform nutrition intervention development. The findings will be presented in conferences, meetings, and published open access. Trial registration This scoping review has been registered in OSF, registration DOI: https://doi.org/10.17605/OSF.IO/FH74T.